2008
DOI: 10.1111/j.1479-828x.2007.00800.x
|View full text |Cite
|
Sign up to set email alerts
|

Abdominopelvic tuberculosis in gynaecology: Laparoscopical and new laboratory findings

Abstract: Introduction: Tuberculosis (TB) is a rare curable infective disease, caused mainly by Mycobacterium tuberculosis, which in abdominopelvic (AP) localisation, can mimic a disseminated carcinomatosis. Symptoms of AP-TB are non-specific, so diagnosis is difficult and elusive as the affected patients have normal chest X-ray and elevated levels of CA125. Female ultrasonographic features of AP-TB mimic peritoneal carcinomatosis, and the computed tomography has also been suggested to be helpful, but the final diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…In one case study, higher levels of T-cell responses were observed using PF-MC rather than PBMC in a patient with TB peritonitis, 7 whereas the PF of all of six patients with TB peritonitis yielded positive ELISPOT results. 24 In the latter report, however, it is unclear which antigens were used in the ELISPOT assay and how many patients PBMCs were positive. To the best of our knowledge, the present study is the first to evaluate the usefulness of the ELISPOT assay for diagnosing abdominal TB and to compare PF-MC assay data with those from PBMC analysis in patients with suspected TB peritonitis.…”
Section: Discussionmentioning
confidence: 97%
“…In one case study, higher levels of T-cell responses were observed using PF-MC rather than PBMC in a patient with TB peritonitis, 7 whereas the PF of all of six patients with TB peritonitis yielded positive ELISPOT results. 24 In the latter report, however, it is unclear which antigens were used in the ELISPOT assay and how many patients PBMCs were positive. To the best of our knowledge, the present study is the first to evaluate the usefulness of the ELISPOT assay for diagnosing abdominal TB and to compare PF-MC assay data with those from PBMC analysis in patients with suspected TB peritonitis.…”
Section: Discussionmentioning
confidence: 97%
“…Visual manifestations of abdominal and pelvic TB at laparotomy and laparoscopy in established cases are well described. [13][14][15][16][17][18] However, subtle signs of subclinical disease have not been identified nor have they correlated with laboratory tests.…”
mentioning
confidence: 99%
“…The most common finding is pelvic adhesions, followed by tubal pathology (i.e. hydrosalpinx, pyosalpinx) or occlusion (by chromopertubation), peritoneal, fallopian tube, or ovarian tubercules, perihepatic adhesions (FitzHugh-Curtis syndrome), tubo-ovarian mass, ascites, and caseous or granulomatous nodules (16)(17)(18). In the case presented above, a complete history would have yielded a higher suspicion of TB at the time of laparoscopy and opportunity to complete more definitive TB testing (i.e.…”
Section: Discussionmentioning
confidence: 99%